Reframing aging - Melby, Melissa K. author aut Link Link Link
1 online resource.
Keywords: How do we age? Why do we age? How and why does menopause happen? Do different cultures have different approaches and attitudes to, and experiences of, aging and menopause? Reframing Aging: Insights from Biology and Culture of Midlife Japanese uses a biocultural framework to try to answer these questions, and gain insights on aging and menopause in Japan, the United States, and beyond.Drawing on years of fieldwork and lab work in Japan, and over a decade of living and working in Japan at several universities and the National Institute of Health and Nutrition, with followup interviews spanning over 20 years, Melissa Melby challenges what are often considered "normal" experiences of aging and menopause. This book introduces a proximateultimate biocultural framework to guide the reader through questions of how (proximate) and why (ultimate) we age, and experience menopause, as we do. Drawing insights from evolutionary biology and societallevel phenomena, and the language of lived experience, it explores how crosscultural variation in expectations, medicalization, collectivism, lifestyles, and other factors may influence how symptoms of aging and menopause are perceived, experienced, and treated.Reframing Aging: Insights from Biology and Culture of Midlife Japanese offers new approaches and insightful perspectives for students of biological/cultural/medical anthropology, gerontology, Asian studies, women and gender studies, medicine, and public health.